Impacto de tratamentos de cama aviária reutilizada na viabilidade e infectividade de micro-organismos - Rech, Daiane Voss (2017)
Reusing litter is a common practice in broiler farming. However, it requires the adoption of efficient procedures for inactivating and controlling residual microorganisms during downtime between flocks to ensure sanitary control over the next flock and the quality of the broiler meat. The broiler production adopts a series of stringent precautionary measures to avoid sanitary emergencies and should be able to employ appropriate control measures. In addition, international consumer markets require proof of the efficiency of treatment methods for broiler litter reuse. The efficiency of broiler litter treatments on pathogens is variable and multifactorial and can be influenced by the treatment method and/or microorganisms evaluated. This study aimed to evaluate the efficiency of different strategies of treatment of broiler litter on Newcastle disease virus (NDV), Infectious bursal disease virus (IBDV) and Salmonella Heidelberg. Total enterobacteria counts were carried out as an indicator of microbiological quality of litter. First, the experimental contamination of the broiler litter by viruses was standardized, comparing the seeder birds inoculated versus the direct spray of the virus in the broiler litter. To evaluate the treatments, reused broiler litter was contaminated with the three microorganisms and submitted to the treatments (T): T1- shallow fermentation; T2- quicklime; T3- shallow fermentation followed by quicklime; and, T4- untreated. The broiler litter was submitted to bacteriological and physico-chemical analyzes during treatment. Sentinel chicks were housed on the broiler litter treated and further monitored by clinical evaluation, as well as microbiological, serological and molecular tests. The results demonstrated that seeder birds were efficient to stablish viral contamination in broiler litter. T1 was superior in reducing total enterobacteria in the broiler litter. The evaluation of sentinel chicks also indicated that T1 and T3 inactivated IBDV in the broiler litter. T2 was not able to reduce the microorganisms evaluated, and its association with T1 (T3) did not enhance the treatment action. NDV did not survive in broiler litter, regardless of the treatment applied. S. Heidelberg survived in broiler litter after all treatments evaluated and was also detected in the sentinel chicks. The antimicrobial activity of T1 and T3 was associated to ammonia levels present in the broiler litter. The results reveal that shallow fermentation is efficient to control residual IBDV and total enterobacteria in recycled broiler litter. However, other strategies should be considered in the presence of S. Heidelberg.